Analysis of Prevention and Handling of Violence Against Children and Its Implementation in Educational Institutions - Al-Aisyi, Azkia Fajri; Nurjanah, Siti; Nurafifah, Lutfia; Agustin, Mubiar (Jurnal Pendidikan Raudhatul Athfal, 2024)
This study aims to analyze efforts to prevent and handle violence against children and their implementation in educational institutions. Efforts to prevent and handle violence against children in the school environment are important, one of which is the formation of a Violence Prevention and Handling Team (TPPK). Previous studies have identified various aspects of preventing and handling violence in schools, including child protection policies in schools. The findings in this study highlight how the implementation of the TPPK program in schools is one of the efforts to prevent and handle violence in schools. The method used is the systematic literature review method by reviewing various related scientific articles from 2018-2024 which were accessed through the Google Scholar database related to the prevention and handling of violence against children and the policies therein. The results of the analysis show that the violence prevention and handling program is being implemented but still requires comprehensive socialization regarding the formation of a Violence Prevention and Handling Team in educational units. Prevention of violence against children can be carried out through a comprehensive approach that involves the active role of schools, families, and the community. The success of the child violence prevention and handling program in educational institutions is highly dependent on the commitment of all stakeholders, firm policies, and continuous monitoring and evaluation.